Inferior Mesenteric Artery Side Branch for Selected Patients with Endovascular Aortic Aneurysm Repair. (2016) - Pfister, K.; Kasprzak, P.M.; Apfelbeck, H.; Kopp, R.; Janotta, M.; Schierling, W.
Abstract : Objective/Background: To report on our experience of the treatment of aortic aneurysms by custom-made, branched stent-grafts with an additional inferior mesenteric artery (IMA) side branch to preserve IMA perfusion in patients at risk for colon ischemia. Methods: Three male patients (mean age 60 years) with a thoracoabdominal, pararenal, and infrarenal aortic aneurysm (AA), respectively, were treated by endovascular aneurysm exclusion using custom-made, branched stent-grafts with a side branch to the IMA for prevention of colon ischemia. Indications for selective IMA side branch perfusion were occlusions or high-grade stenosis of the visceral or hypogastric arteries. Results: No colon ischemia and no neurological deficit were observed. All three IMA side branches were perfused and patent, as documented by computed tomography scan and duplex ultrasound postoperatively and after 12 months. Patency after 24 months was documented as 2/3. Conclusion: Custom-made, branched stent-grafts are an endovascular option to preserve the IMA perfusion in selected, electively treated patients with an increased risk for insufficient colon perfusion due to stenosis or occlusions of visceral or hypogastric arteries. Highlights: Patients with impaired intestinal perfusion are at risk for colon ischemia by endovascular aneurysm repair. Custom-made, branched stent-grafts are an option to preserve inferior mesenteric artery (IMA) perfusion. The IMA side branch technique is an alternative for electively treated patients.